Comparison of high and low-dose epinephrine & endoclip application in peptic ulcer bleeding: A case series analysis observational study. Issue 52 (30th December 2021) - Akay, Tamer; Leblebici, Metin
Abstract : Abstract: Peptic ulcer disease accounts for 50% to 70% of acute upper gastrointestinal bleeding cases. There is no consensus on the treatment of peptic ulcer bleeding (PUB) using endoscopic techniques. This study aimed to compare endoscopic techniques for PUB. Patients with PUB who were hospitalized between January 2014 and June 2020 were included in this study. They were divided into 3 groups: endoclip and low-dose epinephrine injection (0–2 mg, Group 1, n = 62), endoclip and high-dose epinephrine injection (2–4 mg, Group 2, n = 54), and endoclip only (Group 3, n = 64). Early bleeding and permanent hemostasis were higher in Group 2 ( P = .014, .035). When evaluated in terms of late hemostasis and urgent surgical need, there was no significant difference between the groups ( P > .05). Group 2 received a higher amount of blood. Thirty-day mortality occurred in 16.5%, 22.2%, and 9.4% of patients in Groups 1, 2, and 3, respectively. Group 2 had a longer hospital stay than Groups 1 and 3 ( P = .008). The endoscopic success rates were 80.6%, 72.2%, and 90.6% in Groups 1, 2, and 3, respectively. In PUB, if the patient's Rockall score is high and the ulcer size is larger than 2 cm, endoclip application can be used as the main treatment. Addition of epinephrine may be considered when necessary.